Features Of The Formation Of Creative Activity In Primary School Students (Eurasian Journal of Learning and Academic Teaching, 2022)
The specifics of the formation of creative activity in primary school students, methods of conducting current and final reflex exercises for students to understand the essence of their personal creative activity are given.